2021
DOI: 10.1007/s10792-021-02078-4
|View full text |Cite
|
Sign up to set email alerts
|

Graft survival and clinical outcomes of Descemet membrane endothelial keratoplasty: long-term results

Abstract: Purpose: The aim is to report long-term graft survival rates, clinical outcomes of Descemet membrane endothelial keratoplasty (DMEK).Methods: In this study 150 eyes, that underwent DMEK whether for Fuchs endothelial corneal dystrophy (FECD) or for bullous keratopathy (BK), surveilled for 7 years at 6 time-points to evaluate graft survival rates and clinical outcomes of post-corneal transplantation.Results: Overall, the estimated survival probability of 95% con dence interval at 7 years of post-DMEK was 0.58 (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(34 citation statements)
references
References 29 publications
3
29
1
1
Order By: Relevance
“… NS Birbal 2020 [ 11 ] 393 mixed 5 y Multi. NS NS NS < 0.0001 Besek 2022 [ 12 ] 150 mixed 7 y Multi. 0.009 NS NS NS Gund 2021 [ 13 ] 463 mixed 12 mo Multi.…”
Section: Discussionunclassified
See 4 more Smart Citations
“… NS Birbal 2020 [ 11 ] 393 mixed 5 y Multi. NS NS NS < 0.0001 Besek 2022 [ 12 ] 150 mixed 7 y Multi. 0.009 NS NS NS Gund 2021 [ 13 ] 463 mixed 12 mo Multi.…”
Section: Discussionunclassified
“…Like us, four observed that an older age predicted worse final BCVA [ 2 , 3 , 18 , 20 ]. However, one found no association [ 11 ] and another reported that a younger age predicted worse final VA [ 12 ]. The importance of age was noted by two studies as moderate and small [ 3 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations